Pakkiok Bunting Penyambutan Pengantin dalam Suku Makassar: Analisis Albert Parry Lord: Pakkiok Bunting Groom Welcoming in Makassar Tribe: Albert Parry Lord Analysis - Syamsurijal Syamsurijal; Hasina Fajrin R (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
Pakkiok bunting was one of folklore found in Makassar. In modern era, pakkiok bunting has changed in some components. Therefore, the writer uses pakkiok bunting text issued firstly considering that the text was the oldest documented one. Method used in the writing is descriptive with library study. The result of writing concludes that formula and formula expression mostly found in pakkiok bunting are repetition, same words or its synonym. Besides that, some stylistics like metaphor, hyperbole, personification, litotes, associations, etc. are also found in the text. The writer also concludes that the easiness of the poet to perform pakkiok bunting caused by the content is like a series of stories started from welcoming the groom, the marriage, the meeting of bride and groom, and advices of being husband and wife, being the parents, to first meeting of woman and man.